Der fliegende Hut - Berner, Rotraut Susanne 1948- (Hanser, 2002)
A man's hat is blown off by the wind and is worn by various people and animals before it comes back to its owner.
Keywords: Hats -- Juvenile fiction; Stories without words; Hut; Bilderbuch